Expression levels of MiRNA-16, SURVIVIN and TP53 in Preeclamptic and Normotensive women - Ali, Zaima; Zafar, Uzma; Zaki, Saima; Ahmed, Sadia; Khaliq, Saba; Lone, Khalid Pervaiz (Journal of the Pakistan Medical Association, 2021)
Objective: The current study was designed to evaluate and analyze micro RNA-16 (miR-16), survivin, and tumor protein p53 regulated apoptosis-inducing protein 1 (TP53-AIP I, TP53) expression levels in preeclamptic and normotensive pregnancies and to check the correlation of miR-16 with mRNA expression of survivin and TP53. Design of study & place of study: Cross-sectional comparative study. The study was conducted in the Department of Physiology and Cell Biology, University of Health Sciences Lahore (2016-18). Methods: This study comprised of 54 total participants segregated as; 27 preeclamptic and 27 normotensive women. The preeclamptic patients were further organized in to early-onset (EOP) and late-onset preeclampsia (LOP) with 14 and 13 patients respectively. Expression of miR-16, mRNA survivin, and TP53 in preeclamptic and normotensive pregnancies were analyzed by utilizing the real-time polymerase chain reaction. Results: The expression of miR-16 showed a significant increase in the preeclamptic group compared to normotensive pregnancies. The difference was not significant among EOP and LOP. The mRNA expression levels of survivin and TP53 were deregulated in preeclampsia with a decrease in survivin and an increase in TP53. mRNA expression of both survivin and TP53 showed statistically significant differences across the subgroups of preeclampsia. MicroRNA-16 expression correlated negatively with mRNA expression of survivin but exhibited a positive correlation with TP53. Conclusion: The findings conclude that deregulated miRNA-16 along with differentially expressed apoptotic genes, survivin and TP53 might result in altered apoptosis implicated in the pathogenesis of preeclampsia. Continuous...